2010
DOI: 10.1371/journal.pone.0011333
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Dnmt1/PCNA/UHRF1 Interactions Promotes Tumorigenesis from Human and Mice Glial Cells

Abstract: Global DNA hypomethylation is a hallmark of cancer cells, but its molecular mechanisms have not been elucidated. Here, we show that the disruption of Dnmt1/PCNA/UHRF1 interactions promotes a global DNA hypomethylation in human gliomas. We then demonstrate that the Dnmt1 phosphorylations by Akt and/or PKC abrogate the interactions of Dnmt1 with PCNA and UHRF1 in cellular and acelluar studies including mass spectrometric analyses and the use of primary cultured patient-derived glioma. By using methylated DNA imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 33 publications
11
120
0
Order By: Relevance
“…Relationships between signaling molecules and epigenetic regulators have been reported, and PKC signaling is involved in the regulation of promoter activity via detachment of HDAC1 from the promoter region or by the reduction of DNMT activity. [58][59][60] In this study, we observed that a Gln-induced decrease in HDAC1 elicited global histone acetylation and methylation. Consistent with those results, a reduced condensation of the chromatin structure and the regulation of HDAC1 on the Oct4 gene have been reported in undifferentiated ESCs.…”
Section: Discussionmentioning
confidence: 55%
“…Relationships between signaling molecules and epigenetic regulators have been reported, and PKC signaling is involved in the regulation of promoter activity via detachment of HDAC1 from the promoter region or by the reduction of DNMT activity. [58][59][60] In this study, we observed that a Gln-induced decrease in HDAC1 elicited global histone acetylation and methylation. Consistent with those results, a reduced condensation of the chromatin structure and the regulation of HDAC1 on the Oct4 gene have been reported in undifferentiated ESCs.…”
Section: Discussionmentioning
confidence: 55%
“…By interacting with different proteins, DNMT1 may be enriched in or dissociated from specific genomic loci [20][21][22][23][24][25][26] with the distribution of DNMT1 determining the methylation status of specific target sites. For example, the oncogenic PML-RAR fusion protein recruits DNMT1 to the RARb2 promoter to stimulate methylation, 20 whereas disruption of the DNMT1-proliferating cell nuclear antigen (PCNA) interaction results in hypomethylation of cellular DNA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the oncogenic PML-RAR fusion protein recruits DNMT1 to the RARb2 promoter to stimulate methylation, 20 whereas disruption of the DNMT1-proliferating cell nuclear antigen (PCNA) interaction results in hypomethylation of cellular DNA. 24,25 Seemingly, both enzyme activity and chromatin occupancy of DNMT1 are important for DNMT1-dependent changes in DNA methylation observed during tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…UHRF1 binds to the DNA methyltransferase DNMT1 and through the SRA domain interacts with hemimethylated DNA and executes base-flipping of 5-methylcytosines out of the DNA helix during replication (39 -41). UHRF1 null mouse embryos display a severe DNA methylation defect, similar to DNMT1 nulls (42,43). Intriguingly, ectopic expression of UHRF2 does not rescue this UHRF1 null defect, nor does UHRF2 display preferential binding to hemi-methylated DNA over unmethylated DNA as UHRF1, suggesting distinct functions between these proteins (18,19).…”
Section: Figure 9 E2f1 and Uhrf2 Bind To Co-regulated Targets By Chimentioning
confidence: 96%